ANALISIS FAKTOR PENYEBAB KETERLAMBATAN PELAKSANAAN PROYEK REHABILITASI SEKOLAH DALAM MASA PANDEMI COVID-19 - Gusni Vitri; Wendi Boy; Wiwin Putri Zayu (Racic : Rab Construction Research, 2020)
Implementation of construction projects requires resources of materials, labors, equipments, methods and capital to achieve project objectives, namely on time, on quality and according to planned costs. Various internal and external factors influence during project implementation. The conditions of the Covid-19 pandemic that occurred in Indonesia and the world were one of the factors inhibiting project completion. The Primary School Rehabilitation Project in West Pasaman Regency is spread over 15 (fifteen) locations in all sub-districts. The project was contracted in early 2020, before the Covid-19 outbreak erupted. This project has been delayed due to the implementation with 2 (two) addendums to extend the implementation time. This research is descriptive quantitative and qualitative, with data collection techniques through questionnaires and direct interviews with respondents, that are Contractor, Construction Management Consultant and Owner (Ministry of Public Works, Housing and Building Information Center Work Unit West Sumatra Province). The results showed that the most dominant cause of project delays was Force Majeure, Government Policy, Design. Apart from that, other factors that also influence are the weather, the characteristics of the place and the materials.